Doing Business in Mozambique 2019 : Comparing Business Regulation for Domestic Firms in 10 Provinces with 189 Other Economies - World Bank Group (World Bank, Washington, DC, 2019)
Doing Business in Mozambique 2019—the first subnational Doing Business study for Mozambique—assesses the regulatory environment for small and medium-size enterprises in the country. It measures ten provinces in the areas of starting a business, registering property and enforcing contracts: Cabo Delgado, Gaza, Inhambane, Manica, Maputo City, Niassa, Nampula, Sofala, Tete and Zambezia. It also measures trading across borders in three major seaports, Beira port, Maputo port and Nacala port, as well as one land border crossing, Ressano Garcia.